2020
DOI: 10.1130/g47706.1
|View full text |Cite
|
Sign up to set email alerts
|

Time-evolving surface and subsurface signatures of Quaternary volcanism in the Cascades arc

Abstract: Increased resolution of data constraining topography and crustal structures provides new quantitative ways to assess province-scale surface-subsurface connections beneath volcanoes. We used a database of mapped vents to extract edifices with known epoch ages from digital elevation models (DEMs) in the Cascades arc (western North America), deriving volumes that likely represent ~50% of total Quaternary eruptive output. Edifice volumes and spatial vent density correlate with diverse geophysical data that fingerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Till et al, [2019] show evidence for higher mantle melt flux into the crust beneath the southern to central Cascades compared to the central to northern Cascades where volcanic centers are more spatially isolated. O'Hara et al, [2020] find that vent density is correlated with negative Rayleigh phase velocities suggesting upper to middle crustal structural attributes are linked to variable focusing of volcanism along the arc. The present study area, previously referred to as the Columbia segment of the Cascades arc [Schmidt et al, 2008] is located near the transition from more distributed vents and higher magmatic flux in the south to more localized vents and lower flux in the north [O'Hara et al, 2020].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Till et al, [2019] show evidence for higher mantle melt flux into the crust beneath the southern to central Cascades compared to the central to northern Cascades where volcanic centers are more spatially isolated. O'Hara et al, [2020] find that vent density is correlated with negative Rayleigh phase velocities suggesting upper to middle crustal structural attributes are linked to variable focusing of volcanism along the arc. The present study area, previously referred to as the Columbia segment of the Cascades arc [Schmidt et al, 2008] is located near the transition from more distributed vents and higher magmatic flux in the south to more localized vents and lower flux in the north [O'Hara et al, 2020].…”
Section: Introductionmentioning
confidence: 83%
“…Subduction zone plate boundaries extend for hundreds to thousands of kilometers along strike fueling volcanic arcs on the overriding plate. Slab inputs to the mantle that are continuous along strike give rise to discrete volcanoes with variable distance from the plate boundary and along-strike spacing [e.g., Lee and Wada, 2017;O'Hara et al, 2020], as well as compositional heterogeneity within and between different volcanoes [e.g., Wanke et al, 2019;Pitcher and Kent, 2019]. Heterogeneity also occurs at intermediate scales in which groups of adjacent volcanoes with common geochemical or eruptive characteristics define along-strike segments [Schmidt et al, 2008;Pitcher and Kent, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…If hundreds of volcanic centres are analysed, as it is the case here, different approaches and methods are needed to take spatial and temporal variations in hazard into account. On the broadest scale, different techniques have been developed to forecast the location and timing of future volcanic activity in arc segments (e.g., Martin et al, 2004;Jaquet et al, 2012;Germa et al, 2013;Jaquet et al, 2017;Kósik et al, 2020;O'Hara et al, 2020). Of these, the approach of Martin et al (2004) is particularly useful for the purposes of our application as it performs an estimation of the spatio-temporal hazard by modeling each volcanic vent as monogenetic or polygenetic.…”
Section: Methodsmentioning
confidence: 99%
“…If dozens or hundreds of volcanic centres are analysed, new approaches and methods are needed. Techniques have been developed to forecast the location and timing of future volcanic vent opening in arc segments (Martin et al, 2004;Jaquet et al, 2012, Jaquet et al, 2017Germa et al, 2013;Kósik et al, 2020;O'Hara et al, 2020), which is the first step towards regional assessments. There is a further need to integrate spatial and temporal histories into these types of analyses, along with a comprehensive and systematic methodology to evaluate different types, frequencies and scales of volcano processes associated with each vent/volcano.…”
Section: Introductionmentioning
confidence: 99%
“…O’Hara et al. (2020) found that vent density is correlated with negative Rayleigh phase velocities, suggesting that upper to middle crustal structural attributes are linked to variable focusing of volcanism along the arc. The present study area, previously referred to as the Columbia segment of the Cascades arc (Schmidt et al., 2008), is located near the transition from more distributed vents and higher magmatic flux in the south to more localized vents and lower flux in the north (O’Hara et al., 2020).…”
Section: Introductionmentioning
confidence: 99%